Effect of Swiftlet’s (Collocalia Fuciphago) Nest Extract on the Malondialdehyde (MDA) and Superoxyde Dismutase (SOD) Activity on Hyperglycemic Rattus Norvegicius - Francisca Diana Alexandra; Agnes Frethernety; Elsa Trinovita; Triawanti Triawanti (Majalah Obat Tradisional, 2020)
Hyperglycemia that occurs in diabetic Mellitus leads to glycation reactions in protein molecules and oxidative stress resulting in damage to cells and organs. Swiftlet’s nest believed society could lower blood glucose. The objective of the study was to evaluate the effect of Swiftlet’s nest (Collocalia fuciphago) extract on glucose level, Malondialdehyde (MDA) levels, and Superoxide Dismutase (SOD) activity in blood serum. The study used Posttest-Only with Control Group Design, consisting of 1 control group (given aqua dest) and 3 treatment groups (dose 1; 10 and 100 mg/kg BW). Each group consisted of 6 Rattus norvegicius. Before being treated, Streptozotocin-induced rat at a dose of 68 mg/kg BW intraperitoneal. On the 7th day after induction, rats had elevated glucose ± 102 - 108 mg/dL. Then the rats were given water extract Swiftlet’s nest for 28 days orally. All data were analyzed by the Kruskal-Wallis test, followed by the Mann-Whitney test, with a 95% confidence level. The results of blood glucose levels in each group (K, P1, P2 and P3) were 111.0 vs 88.5 vs 86 vs 83 mg / dL (p = 0.035), MDA levels experienced an increase in the treatment group compared to controls namely 193.50 vs 193.83 vs. 198.50 nmol / mL, p = 0.001. While the SOD enzyme activity has increased, namely 0.0050 vs. 0.0075 vs. 0.0263%. In conclusion, Swiftlet’s nest water extract can reduce blood glucose levels and increase MDA levels and SOD enzyme activity in blood serum.